Co9Se8 nanoparticles as high capacity anode material for lithium-ion batteries - Kumar, Pushpendra; Hu, Lung-Hao (Materials Research Express, 2018)
Present investigation deal with the facile synthesis of Co9Se8 nanoparticles (NPs) and their application as the potential anode for lithium-ion battery (LIB). The primary size of the Co9Se8 NPs can be achieved between 10 similar to 25 nm while the secondary cluster size ranging from 150 similar to 200 nm as observed by transmission electron microscope (TEM). The specific capacity of Co9Se8 NPs LIB anode can reach around similar to 610 mAhg(-1) during charging (lithium ion released from Co9Se8 nanoparticles), and -730 mAhg(-1) during discharging (lithium ion intercalated) at an applied current density of similar to 100 mAg(-1). These values are significantly higher than that of the commercial graphite anode (theoretical capacity similar to 372 mAhg(-1)). The irreversibility of Co9Se8 anode (similar to 15%) is also significantly lower than that of most metal oxides and silicon-based anodes (irreversibility ranging between 30 similar to 50% or higher for Si). The reason for superior specific capacity and low irreversibility compared to metal oxides and silicon-based materials could be owing to the stable nano-cluster size which help to reduce the diffusion path and internal resistance to lithium ion.
Keywords: irreversibility; lithium-ion battery; lithium-ion diffusion; Nanoparticles; specific capacity

Controlled synthesis of two-dimensional (2-D) ultra-thin bismuth selenide (Bi2Se3) nanosheets by bottom-up solution-phase chemistry and its electrical transport properties for thermoelectric application - Bin Masood, Khalid; Kumar, Pushpendra; Giri, Rajiv; Singh, Jai (FlatChem, 2020)
Bismuth Selenide and associated compounds inheriting stacked layered structure represent a unique class of materials where bulks are insulating with conducting surfaces, best known as thermoelectric materials. The bottom-up solution-based approach is a convenient alternative producing ultrathin high quality two-dimensional Bi2Se3 nanosheets. The present investigation deals with glycol mediated synthesis of highly crystalline ultrathin Bi2Se3 nanosheets. The as-synthesized Bi2Se3 nanosheets exhibit a rhombohedral crystal structure with a substantial surface-to-volume ratio that can possess several potential applications. Besides, the ultrathin Bi2Se3 nanosheets produced herein, found to be n-type with robust spatial confinement of charge carriers advantageous for thermoelectric applications, delivering a high-power factor of 1.55 mu W/cmK(2) at 150 degrees C. The method demonstrates the generic feature of the solution phase technique for the synthesis of highly crystalline nanosheets allowing mass production of identical ultra-thin nanosheets that can be easily integrated into devices for several promising applications, including spintronics, energy storage, and topological quantum computation.
Keywords: Rhombohedral structure; Sheet-like structure; Thermoelectric nanomaterials; transmission electron microscopy; XPS Spectra

Comprehensive tutorial on the pulsed laser deposition technique and developments in the fabrication of low dimensional systems and nanostructures - Masood, Khalid Bin; Kumar, Pushpendra; Malik, Mushtaq Ahmad; Singh, Jai (Emergent Materials, 2021)
Pulsed laser deposition (PLD) is a simple and extremely versatile technique to grow thin films and nanomaterials of a wide variety of materials. PLD allows the deposition of profoundly different materials, including high-temperature superconductors, oxides, nitrides, carbides, semiconductors, metals, and even polymers or fullerenes with high deposition rates. Growing thin films using PLD is now being used around the world for prototyping thin films of many inorganic materials and even in device fabrication protocols. This article covers the detailed development, versatility, and reliability of the ultraviolet (UV) excimer laser. It is envisioned that this review article is of interest for both the materials and chemical scientists engaged in more fundamental aspects of pulsed laser ablation and deposition. The present article highlights the historical developments of PLD technique, complete mechanism of thin film fabrication, optimization of the quality of thin films and the fabrication of thin films of the materials like ZnO, Graphene, MoS2, and WS2 which are being explored for various potential applications.